2019
DOI: 10.1097/md.0000000000017091
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of high-dose tigecycline for the treatment of infectious diseases

Abstract: Background:High-dose (HD) tigecycline regimen is increasingly used in infectious diseases, however its efficacy and safety versus low-dose (LD) is still unclear.Methods:A systematic review and meta-analysis was performed; PubMed, Embase, Cochrane Library, ScienceDirect, Web of Science, clinicalTrials.gov, Wanfang, VIP, and China National Knowledge Infrastructure (CNKI), were searched using terms “tigecycline” AND “dose” up to October 31, 2018. Eligible studies were randomized trials or cohort studies comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
2
18
0
1
Order By: Relevance
“…3 Institute of Farmacologia, Università Cattolica del Sacro Cuore, L.go F. Vito 1, Rome, Italy. 4 Fondazione Policlinico Universitario Agostino Gemelli IRCCS, Rome, Italy. 5 Dipartimento di Scienze di Laboratorio e Infettivologiche, UOC di Malattie Infettive, Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome, Italy.…”
Section: Supplementary Informationunclassified
See 1 more Smart Citation
“…3 Institute of Farmacologia, Università Cattolica del Sacro Cuore, L.go F. Vito 1, Rome, Italy. 4 Fondazione Policlinico Universitario Agostino Gemelli IRCCS, Rome, Italy. 5 Dipartimento di Scienze di Laboratorio e Infettivologiche, UOC di Malattie Infettive, Fondazione Policlinico Universitario A. Gemelli IRCCS, Rome, Italy.…”
Section: Supplementary Informationunclassified
“…Tigecycline (TGC), the first antimicrobial of glycilcycline class, has shown an expanded-spectrum activity against gram-positive, gram-negative, aerobic, anaerobic and atypical bacterial species, including antibiotic-resistant strains [ 1 ]. Indeed, it has been demonstrated that methicillin-resistant Staphylococcus aureus (MRSA), penicillin-resistant Streptococcus pneumoniae , vancomycin-resistant enterococci (VRE), extended-spectrum β-lactamase (ESBL)/carbapenem-producing Enterobacterales and extensively drug-resistant (XDR) Acinetobacter baumannii are susceptible to TGC [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the administration of tigecycline treatment has been associated with an increased death rate [5], and a number of case reports have indicated serious complications in patients as a consequence of tigecycline treatment [36][37][38][39][40]. On the other hand, a meta-analysis by Falagas et al in 2014 concluded that high-dose tigecycline regimens may be effective for the treatment of severe bacterial infections [9], and a meta-analysis by Gong et al concluded that high-dose tigecycline regimens did not elevate the risk of toxic side effects [41]. Further, pharmacokinetic and pharmacodynamic studies have indicated that higher dosages of tigecycline can be administered to humans, resulting in improved therapeutic efficacy [6,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing incidence of MDR and extensively drug resistant (XDR) strains causing infections has recently renewed the use of tigecycline, often in combination chemotherapy. A recent metanalysis including 17 studies with 1104 pts has demonstrated that high doses of tigecycline (150–200 mg loading dose and then 75–100 mg BID) are more effective both microbiologically and clinically than standard doses without a significant impairment of safety [ 64 ].…”
Section: Pk/pd Issues and Antimicrobial Resistancementioning
confidence: 99%